Léxico toponímico de Diamantina: língua, cultura e memória - Tatiana Martins Mendes (2010)
This research aims to study toponyms from the City of Diamantina and its districts, situated in the valley of the Jequitinhonha river, a region of the State of Minas Gerais, Brazil. This region is historically important due to its strategic location during the period mineral explorationduring the 18th and 19th centuries. Toponimic studies show traces of the local social and cultural history, including constitution of space and settlement as well as vegetation, hidrography, geomorphology, fauna, etc., and they also contribute to the preservation of thememory of the people, since the names of places, when related to language, culture and society, seem to be legitimate registers of past events. The theoretical and methodological isbased on concepts defended by Dauzat (1926) and Dick (1990a, 1990b, 2004) and on the theories on environment elaborated by Sapir (1969). From a sociolinguistic perspective, according to the Labovian model, the research should start at the present moment, expandingtowards the past. Firstly, data on vernacular language was collected in oral interviews; then old maps were referred to for data on written language. The data on past and present elementswere then compared, aiming to examine cases of variations, changes, or linguistic retentions.Results show the predominance of names of places based on the names of plants, names of people and names of geographical elements. The research also shows a small number of cases f variation and of linguistic changes, indicating that the local toponimic is quite conservative.